Knowledge Of Radio Protective Techniques And Awareness Of Radiation Hazards Among Radiologists And Non-Radiology Healthcare Professionals In Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
Background: Medical imaging procedures involving the use of ionizing radiation are associated with potentially harmful biological effects, especially after long-term exposure or high doses of radiation. The use of medical radiation in diagnosis and procedural and surgical treatment is increasing. Therefore, healthcare personnel should be adequately aware and knowledgeable about radiation hazards to protect themselves and their patients from its adverse effects.  The application of ionizing radiation in healthcare has grown. Healthcare professionals must therefore be aware of the risks associated with radiation and take the appropriate precautions to lower occupational exposure. This study aimed: To assess the knowledge of radio protective techniques and awareness of radiation hazards among radiologists and non-radiology professionals. These findings may improve the application of various safety measures during medical interventions involving radiation. Methods: A cross-sectional questionnaire‑based study among 200 medical personnel was conducted, including consultant surgeons, physicians, radiologists, nurses, and radiographers, across five hospitals in Saudi Arabia from January to April 2024. The questionnaire collected data on demographic characteristics, awareness of radiation hazards, and knowledge of radio protective techniques. Results: Overall, the knowledge of radiation protection and awareness of radiation hazards among the participants were poor (51.55% and 37.17%, respectively). No significant difference was detected between the medical disciplines in terms of the level of knowledge of radiation protection; however, radiographers were significantly more aware of radiation hazards. Conclusions: According to the present findings, medical personnel generally have poor awareness of radiation hazards and radiation protection protocols. However, this understanding can be enhanced through periodic in-service training and regular monitoring of occupational radiation exposure by health professionals.